Piv-based investigation of haemodynamic factors in diseased carotid artery bifurcation - Ahmad Fahmi Huwaidi, Mohamad Noor (2024)
Ischemic stroke, often precipitated by the development of plaque within the carotid arteries leading to carotid artery stenosis, represents a significant health concern. This condition is heavily influenced by hemodynamic parameters such as velocity profiles, wall shear stress, and pressure within the blood flow.Addressing this, the current study endeavors to elucidate the flow characteristics at carotid artery bifurcations by employing particle image velocimetry (PIV) and computational models, and to ascertain the impact of stenosis placement on these hemodynamic parameters. The initial phase of this research involves the examination of flow patterns in a post-stent carotid artery bifurcation phantom using both 2D PIV and 3D stereo-PIV (SPIV). These findings are subsequently juxtaposed with those derived from computational fluid dynamics (CFD) analyses, concentrating on areas of interest that include the inlet, bifurcation, and stented segments. Additionally, this study constructs and examines idealized models of varying stenosis locations, evaluating them based on the velocity profiles, wall shear stress, and pressure at the sites of stenosis. Results reveal a reduced flow velocity in the bifurcation area, with consistent trends between PIV and SPIV methodologies. A notable yet acceptable variance of about 16.66% in average flow velocity was discerned between the 2D and 3D PIV approaches.Despite SPIV's enhanced precision in vector capture, this minor disparity validates the use of PIV for comprehensive CFD comparison within the purview of this research. Comparative analysis of velocity vectors in the post-stent area demonstrates analogous trends between PIV and CFD, while the inlet region displays more significant differences, notably the higher velocities detected by CFD. Here, CFD anticipates a maximum velocity of 0.98 m/s, approximately 10% higher than that measured by PIV. The observed low-velocity zones around bifurcations and curvatures are conducive to recirculatory flow, fostering atherosclerotic progression. Moreover, the research identifies that Type I stenosis upstream stenosis is more prone to result in intraplaque hemorrhage (IPH), potentially exacerbating patient outcomes. The insights from this study enhance our comprehension of vascular mechanics and hold the potential to refine clinical approaches to managing carotid artery disease.